Household food insecurity, coping strategies, and nutritional status of pregnant women in rural areas of northern Ghana - Saaka, M.; Oladele, J.; Larbi, Asamoah; Hoeschle-Zeledon, Irmgard (Wiley, 2017)
There is limited information on the magnitude and determinants of household food insecurity (HFI) and how it relates to the nutritional status of pregnant women in Northern Ghana. The magnitude, determinants of HFI, and how it relates to the nutritional status of pregnant women were evaluated in the Africa RISING West Africa project intervention communities in Northern Ghana. The prevalence of moderate and severe household hunger was 25.9% (95% CI: 19.0, 34.3) and 6.8% (95% CI: 4.2, 10.9) respectively. The independent predictors of maternal thinness were region of residence, gestational age and maternal age. Compared to women in the first trimester, women in the third trimester were 2.2 times more likely of being underweight adjusted odds ratio (AOR = 2.19, CI: 1.02, 4.70). Women who were under 20 years of age were 11.9 times more likely of being thin compared to women aged more than 35 years (AOR = 11.97, CI: 2.55, 5. 67). Food insecurity was highly prevalent but it was not associated with maternal thinness of pregnant women. The risk of maternal thinness increased as the gestational age increased and this has a great potential of adversely influencing pregnancy outcomes and overall quality of life.